From the Idea of Start-Up to Setting-Up Unicorn-Company - E. Yu. Kulakova (Plekhanov Russian University of Economics, 2021)
The article investigates history of establishment and development of start-up unicorn-companies with capitalization over $ 1bn. The authors analyzed key types of unicorn-companies (unicorns, decacorns quinquagintacorns, gectacorns), identified their principle characteristics, showed criteria and factors of their success. The role of venture funds was studied, as they are major investors into promising business-projects. The article described trends of the 1-st half of 2020, the time of state restrictions and pandemic, such as distant work, IT entertainments, could services, on-line delivery, marketplaces, drop in business activity, which require clients' presence. It also showed the process of business-projects' passing from start-ups to companies with high capitalization. The authors pointed out that to create a successful company with capitalization of $ 1bn you do not need any special conditions, but there is certain logic concerning how the start-up can become unicorn-company. Basic points of this logic were provided. The authors substantiated the necessity of venture fund promotion among entrepreneurs and investors in order to speed up the start of start-ups and development of business-projects to the level of big companies.